Komunikasi Interpersonal Game GTA V Roleplay Dalam Membangun Relationship Pertemanan Antar Pemain - Putra, Agung Kuntala; Fauzi, Ramdan; Dean, Khansa Sajidah; Triwardhani, Ike Junita (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study discusses interpersonal communication between players in the GTA V Roleplay game as a medium for forming friendships. In roleplay mode, players not only carry out missions, but also act as characters in a social simulation that resembles real life. With a qualitative approach and case study method, data were collected through observation and in-depth interviews with three active players. Joseph A. DeVito's (2011) interpersonal communication theory was used as an analytical framework, covering five dimensions: openness, empathy, support, positive attitude, and equality. The results of the study show that interactions in GTA V Roleplay form authentic social relations, even continuing outside the virtual world. Communication that occurs in the game creates emotional bonds and friendships that are equal, warm, and mutually supportive. In conclusion, online games are not only a means of entertainment, but also a social space that allows for meaningful interpersonal communication.